2015
DOI: 10.1016/j.jval.2015.09.711
|View full text |Cite
|
Sign up to set email alerts
|

Health State Utilities Associated With Glucose Monitoring Devices

Abstract: A363life. When possible, meta-analysis was performed, evaluating the presence of heterogeneity and risk of publication bias. Otherwise, descriptive analysis of the available data was done. Results: Of the 10.348 original references scanned, 17 studies were finally selected, 7 experimental and 10 analytical. The population included was mainly adults, with type 2 diabetes. Important risk of bias was found in all of the articles, particularly the experimental ones. Meta-analysis was performed for glycemic control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This difference was converted to a utility gain in the RT-CGM arm of 0.02536, based on a published mapping of the HFS (using only the eight-question worry subscale) to the EuroQol 5-dimension questionnaire (EQ-5D) (4), wherein a 1-unit change in HFS score corresponded to a 0.008-unit change in EQ-5D index score. Patients in the RT-CGM arm were also assumed to have an additional utility benefit of 0.03 owing to avoiding fingerstick SMBG testing multiple times per day, based on published data by Matza et al (12). Matza et al used time tradeoff methodology to compare utility values between patients using flash glucose monitoring with those using SMBG (based on a usage of three SMBG tests per day), and it was assumed that the utility value of patients using flash glucose monitoring would be equal to that of patients using RT-CGM, as both reduce or eliminate the need for SMBG.…”
Section: Health State Utilitiesmentioning
confidence: 99%
“…This difference was converted to a utility gain in the RT-CGM arm of 0.02536, based on a published mapping of the HFS (using only the eight-question worry subscale) to the EuroQol 5-dimension questionnaire (EQ-5D) (4), wherein a 1-unit change in HFS score corresponded to a 0.008-unit change in EQ-5D index score. Patients in the RT-CGM arm were also assumed to have an additional utility benefit of 0.03 owing to avoiding fingerstick SMBG testing multiple times per day, based on published data by Matza et al (12). Matza et al used time tradeoff methodology to compare utility values between patients using flash glucose monitoring with those using SMBG (based on a usage of three SMBG tests per day), and it was assumed that the utility value of patients using flash glucose monitoring would be equal to that of patients using RT-CGM, as both reduce or eliminate the need for SMBG.…”
Section: Health State Utilitiesmentioning
confidence: 99%
“…In contrast, vignette-based methods are well-suited for isolating the utility impact of specific treatmentrelated attributes and are commonly used in studies of treatment process utilities [1]. Several previously published studies used this approach to estimate the utility impact of diabetes treatment attributes [21][22][23][24]. The utilities derived in these previous studies have been used in a range of published cost-utility analyses (CUAs) of treatments for diabetes [25][26][27][28][29][30].…”
Section: Overview Of Study Designmentioning
confidence: 99%
“…The literature shows that for the first few minor hypoglycaemic events, individuals experience relatively high disutilities; the disutility per event diminishes as the individual starts having more events. In addition, an intervention-related health utility benefit of 0.03 was applied to the FSL arm [17] (Supplementary Table S4).…”
Section: Utilitymentioning
confidence: 99%
“…Several studies have demonstrated that people with diabetes have a better experience using FSL than they do with SMBG, since a scan using FSL is not only less stressful, painless and easier to understand [15], but it is also less time-consuming than traditional SMBG [16]. Further, a time trade-off analysis reported a significantly higher utility value for diabetes glucose monitoring using FSL compared with SMBG, suggesting that the use of FSL is associated with an improvement in health-related quality of life [17].…”
Section: Introductionmentioning
confidence: 99%